2005
DOI: 10.1111/j.1365-2141.2004.05319.x
|View full text |Cite
|
Sign up to set email alerts
|

MDR1 and MRP1 gene expression are independent predictors for treatment outcome in adult acute myeloid leukaemia

Abstract: Summary Multi drug resistance (MDR) is a major obstacle for cancer therapy. The three major candidates accounting for the development of MDR in acute myeloid leukaemia (AML) are multi drug resistance gene (MDR1), multi drug resistance‐related protein gene (MRP1) and lung resistance protein gene (LRP). So far, the differential impact of resistance gene expression on treatment outcome in AML is not clear. Therefore, we examined MDR1, MRP1 and LRP gene expression at diagnosis in 331 adult AML patients in the cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
80
1
3

Year Published

2006
2006
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(90 citation statements)
references
References 40 publications
6
80
1
3
Order By: Relevance
“…24 A German study found a positive correlation between the expression of another MDRrelated protein, MRP1, and resistance to FLT3 inhibitors. 25 The additive negative effect on DFS that we observed in ABCG2þ/FLT3þ patients could be explained by a regulatory role of FLT3 mutation on ABCG2. In fact, the constitutive activation of intracellular transcriptional pathways induced by mutated FLT3 may justify the expansion of the entire leukemia progenitor population (explaining the higher WBC count in mutated cases) and the activation of the antiapoptotic machinery in these cells.…”
Section: Discussionmentioning
confidence: 73%
“…24 A German study found a positive correlation between the expression of another MDRrelated protein, MRP1, and resistance to FLT3 inhibitors. 25 The additive negative effect on DFS that we observed in ABCG2þ/FLT3þ patients could be explained by a regulatory role of FLT3 mutation on ABCG2. In fact, the constitutive activation of intracellular transcriptional pathways induced by mutated FLT3 may justify the expansion of the entire leukemia progenitor population (explaining the higher WBC count in mutated cases) and the activation of the antiapoptotic machinery in these cells.…”
Section: Discussionmentioning
confidence: 73%
“…33). However, in our series, only 35% (9 of 26) of ITD+ patients were classified in the monocytic group and FAB M1 mostly (35). The strongest negative effect was found in the intermediate cytogenetic population, with respect to CR achievement, DFS, and OS.…”
Section: Discussionmentioning
confidence: 73%
“…Recently published data of multi-drug-resistance gene expression showed negative influence on therapy response in complex aberrant patients. 37 Association of p53 deletion and MDR1 expression has been confirmed for CML, but not for AML. 38 An independent negative additive effect with decreased induction of apoptosis and increased cytostatica efflux can therefore be considered.…”
Section: Discussionmentioning
confidence: 90%